Control of the interface between heterotypic cell populations reveals the mechanism of intercellular transfer of signaling proteins1. Issue 3 (9th March 2015) - Kshitiz; Afzal, Junaid; Suhail, Yasir; Ahn, Eun Hyun; Goyal, Ruchi; Hubbi, Maimon E.; Hussaini, Qasim; Ellison, David D.; Goyal, Jatinder; Nacev, Benjamin; Kim, Deok-Ho; Lee, Justin Ho; et al.
<x xml:space="preserve">Abstract</x> Direct intercellular transfer of cellular components is a recently described general mechanism of cell–cell communication.